A green and black tea extract benefits urological health in men with lower urinary tract symptoms. (June 2014) - Katz, Aaron; Efros, Mitchell; Kaminetsky, Jed; Herrlinger, Kelli; Chirouzes, Diana; Ceddia, Michael
Objectives: The objective of this study was to examine the effects of a green and black tea extract blend [AssuriTEA Men's Health (AMH)] in men with lower urinary tract symptoms (LUTS). Methods: In this randomized, double-blind, placebo-controlled study, 46 men aged 30–70 with an American Urologic Association symptom score (AUAss) of at least 8 and up to 24 were randomized to 500 mg AMH, 1000 mg AMH, or placebo daily for 12 weeks. Measurements were taken at baseline (BL), week 6 and week 12 for AUAss, simple uroflowmetry, postvoid residual volume (PVR), C-reactive protein (CRP), Short-Form 36 Health Survey (SF-36), and International Index of Erectile Function (IIEF). Results: A total of 40 subjects completed the study. AUAss decreased 34.5% from BL to week 12 in the 1000 mg AMH group ( p = 0.008). At week 12, CRP increased in the 500 mg AMH ( p = 0.003) and placebo ( p = 0.012) groups from their BL levels but not in the 1000 mg group. Average urine flow (Qmean) increased in the 500 mg ( p = 0.033) and 1000 mg AMH ( p = 0.002) groups versus placebo. PVR decreased in the 1000 mg AMH group ( p = 0.034) from BL at week 6. Treatment group effects were observed for the physical functioning and sexual desire domains of the SF-36 and IIEF ( p = 0.051 and p = 0.005 respectively). AMH was well tolerated. Conclusions: Oral administration of AMH improved LUTS and quality of life in as little as 6 weeks.